2012
DOI: 10.1128/aac.00891-12
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Separate Domains in Lysin PlyG for Recognizing Bacillus anthracis Spores and Vegetative Cells

Abstract: ABSTRACTAs a potential antimicrobial, the bacteriophage lysin PlyG has been reported to specifically recognizeBacillus anthracisvegetative cells only and to killB. anthracisvegetative cells and its germinating spores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 52 publications
(59 reference statements)
0
39
1
Order By: Relevance
“…This endolysin has multiple binding domains, one for peptidoglycan of vegetative cells and another for the spore surface. 40 In contrast, CBD are not always required for lytic activity, 31,41 and in some cases CBD removal can improve bacteriolytic potency and/or lytic spectrum (see 'Engineering novel endolysin constructs' section below for more details). Endolysins are typically the product of a single gene in a single open reading frame.…”
Section: Endolysins -Peptidoglycan Degrading Enzymesmentioning
confidence: 99%
“…This endolysin has multiple binding domains, one for peptidoglycan of vegetative cells and another for the spore surface. 40 In contrast, CBD are not always required for lytic activity, 31,41 and in some cases CBD removal can improve bacteriolytic potency and/or lytic spectrum (see 'Engineering novel endolysin constructs' section below for more details). Endolysins are typically the product of a single gene in a single open reading frame.…”
Section: Endolysins -Peptidoglycan Degrading Enzymesmentioning
confidence: 99%
“…The recombinant proteins were expressed by the E. coli BL21(DE3) strain in standard LB medium and purified following procedures described previously (24,29), with minor modifications. ClyH was induced overnight in BL21(DE3) cells with L-arabinose in a final concentration of 0.2% at 20°C.…”
Section: Bacterial Strains Bacterial Strains (Seementioning
confidence: 99%
“…The CBDs of the majority of lysins are responsible for attaching the hydrolases to their specific substrates in the bacterial cell walls via non-covalent binding of carbohydrate ligands (Loessner et al, 2002). It has been reported that the number of CBD binding sites on one bacterial cell can be 10 7 or more (Yang et al, 2012). Moreover, the size of CBD (usually 10 to 20 kilodaltons) is much smaller than that of antibodies (usually 150 kilodaltons).…”
Section: Introductionmentioning
confidence: 98%
“…Bacteriophage endolysins or lysins are a class of bacteria cell wall peptidoglycan hydrolase synthesized at the late stage of the bacteriophage lytic cycle, mediating lysis of the host cell and the release of progeny phages (Fischetti, 2008;Yang et al, 2012Yang et al, , 2014b domain and C-terminal cell wall binding domain (CBD) (Yang et al, 2012(Yang et al, , 2014b. The CBDs of the majority of lysins are responsible for attaching the hydrolases to their specific substrates in the bacterial cell walls via non-covalent binding of carbohydrate ligands (Loessner et al, 2002).…”
Section: Introductionmentioning
confidence: 99%